MIXED GONADAL DYSGENESIS IN A SEVEN MONTH OLD BABY - Krishna Levina, Made Ayu; Arimbawa, I Made (Medicina, 2014)
Mixed gonadal dysgenesis is a very rare case with genital ambiguity as a clinical manifestation.Diagnosis of this condition is emerging due to proper gender assignment and  prompt treatment toachieve optimal physical and psychologic development. We reported a genital ambigous in a 7 month old baby, who was referred with enlargement of clitoris, an unpalpable testis, but with a highconcentration testosteron serum level, an uterus from genitography, and a mosaic karyotype 45,X/46,XY. The working diagnosis of this baby is mixed gonadal dysgenesis. Patients is being evaluated by a multidisciplinary team and planned having laparoscopy.  [MEDICINA 2014;45:52-57]